2022
DOI: 10.14701/ahbps.22-041
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, mortality and survival of gallbladder, extrahepatic bile duct, and pancreatic cancer using Korea central cancer registry database: 1999-2019

Abstract: Invited ArticleBackgrounds/Aims: In Korea, pancreatic cancer and "gallbladder and extrahepatic bile duct cancer" were ranked the 8th and 9th most frequent cancers in 2019 and the 4th and 6th most common causes of cancer deaths in 2020, respectively. Methods: This review provides national cancer statistics and secular trends of 207,521 patients with gallbladder (n = 44,178), extrahepatic bile duct (n = 61,856), and pancreatic cancer (n = 101,487) between 1999 and 2019 in Korea. Results:The crude incidence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Bjerregaard et al found a minor improvement in 5-year relative survival from 6-9% to 13-16% from 1980 to 2012 in Denmark's population [28]. Kang et al found an increase in 5-year survival rates from extrahepatic bile duct cancer, from 23.1% to 27.5% (p < 0.01) in the period between 1999 and 2019 in the Korean population [38]. While the overall 5-year relative survival rates are similar worldwide, the survival rates can differ depending on the stage of disease as well as the therapy that a patient received.…”
Section: Discussionmentioning
confidence: 99%
“…Bjerregaard et al found a minor improvement in 5-year relative survival from 6-9% to 13-16% from 1980 to 2012 in Denmark's population [28]. Kang et al found an increase in 5-year survival rates from extrahepatic bile duct cancer, from 23.1% to 27.5% (p < 0.01) in the period between 1999 and 2019 in the Korean population [38]. While the overall 5-year relative survival rates are similar worldwide, the survival rates can differ depending on the stage of disease as well as the therapy that a patient received.…”
Section: Discussionmentioning
confidence: 99%
“…Its incidence and mortality rates have been significantly increasing in recent years [4]. It predominantly affects middle-aged and elderly individuals [5], with a higher prevalence in males than premenopausal females, but similar incidence rates in postmenopausal females [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Common symptoms include yellowing of the skin and sclera, high fever, abdominal pain, and decreased appetite. In cases of complete obstruction, the stool color may become pale or even clay-like[ 1 ]. Percutaneous transhepatic cholangial drainage (PTCD), a widely used palliative care method[ 2 , 3 ], offers advantages such as a straightforward procedure, effective jaundice relief, and convenient bile drainage, making it a popular choice in clinical settings.…”
Section: Introductionmentioning
confidence: 99%